Perilaku Seksual Penderita HIV/AIDS dalam upaya pencegahan penularan di RSUD Arifin Ahmad Provinsi Riau - Aziz, Ari Rahmat; Efliani, Destria; Redho, Ahmad (Jurnal Ilmiah Keperawatan, 2020)
The number of sufferers of Human Immunoficiency Virus (HIV) / AIDS continues to increase every year. One of the causes of new sufferers is the risky sexual behavior of people with HIV / AIDS that has been detected. The purposed of this study is to describe the sexual behavior of people with HIV / AIDS in Arifin Achmad Public Hospital as a prevention of HIV / AIDS transmission. The research method used descriptive analytic techniques to describe the sexual behavior of HIV / AIDS. The study was conducted from January 27, 2020 to February 27, 2020 in Arifin Achmad Public Hospital. The results showed that of 120 respondents, 71 (60%) respondents had risky sexual behavior and 49 (40%) respondents had healthy sexual behavior. Analyze with statistics showed there are not correlation between sex (p value = 0.2) and education (p value = 0.6) level with sexual behavior HIV AIDS patient. These results encourage care giver to be more active in providing health education. Keywords: Sexual behavior; HIV/ AIDS Patient;